Long-term spatiotemporal variation of drought patterns over the Greater Horn of Africa - Gebremeskel Haile, Gebremedhin; Tang, Qiuhong; Leng, Guoyong; Jia, Guoqiang; Wang, Jie; Cai, Diwen; Sun, Siao; Baniya, Binod; Zhang, Qinghuan (The Science of the total environment, 2020)
[Display omitted] •Spatiotemporal drought patterns were investigated in the Greater Horn of Africa.•Droughts showed an increasing annual trend during 1964–2015.•Droughts in 1973–74, 1984–85, and 2010–11 were severe and intense.•Droughts increased in winter, spring and summer but decrease in autumn season.•Information on historical droughts is helpful to adapt and alleviate drought. Understanding historical patterns of changes in drought is essential for drought adaptation and mitigation. While the negative impacts of drought in the Greater Horn of Africa (GHA) have attracted increasing attention, a comprehensive and long-term spatiotemporal assessment of drought is still lacking. Here, we provided a comprehensive spatiotemporal drought pattern analysis during the period of 1964–2015 over the GHA. The Standardised Precipitation-Evapotranspiration Index (SPEI) at various timescales (1 month (SPEI-01), 3 month (SPEI-03), 6 month (SPEI-06), and 12 month (SPEI-12)) was used to investigate drought patterns on a monthly, seasonal, and interannual basis. The results showed that despite regional differences, an overall increasing tendency of drought was observed across the GHA over the past 52 yr, with trends of change of −0.0017 yr−1, −0.0036 yr−1, −0.0031 yr−1, and −0.0023 yr−1 for SPEI-01, SPEI-03, SPEI-06, and SPEI-12, respectively. Droughts were more frequent, persistent, and intense in Sudan and Tanzania, while more severe droughts were found in Somalia, Ethiopia, and Kenya. Droughts occurred frequently before the 1990 s, and then became intermittent with large-scale impacts occurred during 1973–1974, 1984–1985, and 2010–2011. A turning point was also detected in 1989, with the SPEI showing a statistically significant downward trend during 1964–1989 and a non-statistically significant downward trend from 1990 to 2015. Seasonally, droughts exhibited an increasing trend in winter, spring, and summer, but a decreasing trend in autumn. The research findings have significant implications for drought adaptation and mitigation strategies through identifying the hotspot regions across the GHA at various timescales. Area-specific efforts are required to alleviate environmental and societal vulnerabilities to drought events.